2023
DOI: 10.1021/acssuschemeng.2c06875
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Magnetite Production Using Microfluidic Devices: Moving from the Laboratory to Industrial Scale

Abstract: Magnetite nanoparticles (MNPs) have important applications in several industrial and scientific fields for the remediation of contaminated soil and water, for instance. Emerging technologies such as microfluidic techniques have been adapted to continuously synthesize MNPs showing appealing results, such as a narrower size distribution. Therefore, this approach might become important for producing MNPs to meet industrial requirements. In this study, a life cycle assessment (LCA) is conducted to analyze and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“… Environmental analysis using life cycle analysis methodology on the industrial production of biosensors. Reproduced with permission under a Creative Commons CC-BY 4.0 from ref 130 Copyright 2023, American Chemical Society. …”
Section: What the Future Should Bring: Toward Sustainable Biosensingmentioning
confidence: 99%
“… Environmental analysis using life cycle analysis methodology on the industrial production of biosensors. Reproduced with permission under a Creative Commons CC-BY 4.0 from ref 130 Copyright 2023, American Chemical Society. …”
Section: What the Future Should Bring: Toward Sustainable Biosensingmentioning
confidence: 99%
“…This approach fails to account for major overlooked concerns such as the recyclability of nanomaterials and the use of large amounts of solvents needed for purification. Recent studies have made progress in this regard and have achieved successful LCAs looking at several types of materials aiming to inform and enable the design of future, greener procedures. Further, this type of research was overviewed in Dr. Phil Jessop’s lecture entitled “Choosing the Greenest Synthesis through LCA”, in which the intricacies of an LCA were covered and a gate-to-gate analysis was done as a teaching exercise. As nanomaterial use increases, established metrics that incorporates a systems thinking approach ( e.g ., LCA) in this area will be vital for researchers and manufacturers …”
Section: How Green Is Our Research?mentioning
confidence: 99%
“…Using life cycle assessment (LCA), processes and products with a quantitative impact can be evaluated. Recent environmental awareness has led to LCA studies being conducted on a variety of products such as food, , chemicals, , coffee, , and pharmaceuticals. , In recent years, many researchers have published articles on LCA of various active pharmaceutical ingredients and articles related to the comparative life cycle assessment of various chemical compounds. A scale up framework has also been evaluated using LCA studies. Sahu et al (2023) have carried out a LCA for the antisolvent crystallization for the selective salt recovery . The LCA study associated with crystallization using SimaPro was reported by De Marco (2022) .…”
Section: Introductionmentioning
confidence: 99%